Фрагмент графіто з новими іменами в Ольвії - Русяєва, А.С. (Археологія і давня історія України, 2016)
Подано першу публікацію нового фрагментованого напису на маленькому уламку стінки аттичної чорнолакової чаші. В начале 2015 г. в Археологическом музее ИА НАНУ обнаружено граффито на очень маленьком обломке стенки аттической чернолаковой чаши без инвентарного номера. At the beginning of 2015, in the Archaeological Museum of the IA NASU, a graffito on a very small body fragment of Attic black-glazed cup without the inventory number was found. Apparently, it was accidentally found in Olbia in the area of south-western part of Agora and was passed to N.O. Leipunska after the excavations were finished. An inscription broken on the left side consisted of five lines and was made extremely carelessly without a preliminary lay-out. Judging from the script nature, together with paleographic analogies and the glaze quality of Attic black-glazed ceramics, the inscription can be dated within the period from the last quarter of the 6th to the first half of the 5th centuries BC.